Discovering Culture and English: My Learning Experience at Ahmad Dahlan University through UMT's Study Abroad Program - Indra, Yudhie; Syahan, Rizka Salsabiila; Triana, Audia; Dalpah, Dalpah; Ardelia, Sita (Universitas Muhammadiyah Tangerang, 2024)
The aim of this research is to open the door for writers to explore their public speaking in Indonesian culture, especially in the UAD campus environment. They detailed interactions with local students, participation in cultural activities, and learning about the traditions and values that underlie Indonesian society. In addition, the author also notes the positive influence that Indonesian culture has on their world perspective. The method used is a qualitative method. The results of this research show that the authors share their challenges and achievements in improving their English language skills. They evaluated how this experience improved their English and public speaking skills, which would be useful in the current context of globalization and provided insight into valuable cross-cultural and linguistic learning experiences through comparative study programs. It also underscores the importance of cultural exchange in opening up global understanding and developing language skills for students participating in such programs.